2019
DOI: 10.5194/hess-23-4249-2019
|View full text |Cite
|
Sign up to set email alerts
|

Simulating preferential soil water flow and tracer transport using the Lagrangian Soil Water and Solute Transport Model

Abstract: Abstract. We propose an alternative model concept to represent rainfall-driven soil water dynamics and especially preferential water flow and solute transport in the vadose zone. Our LAST-Model (Lagrangian Soil Water and Solute Transport) is based on a Lagrangian perspective of the movement of water particles (Zehe and Jackisch, 2016) carrying a solute mass through the subsurface which is separated into a soil matrix domain and a preferential flow domain. The preferential flow domain relies on observable field… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
74
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(84 citation statements)
references
References 47 publications
10
74
0
Order By: Relevance
“…The LAST-Model (Sternagel et al, 2019) is based on the Lagrangian approach of Zehe and Jackisch (2016), which was introduced to simulate infiltration and soil water dynamics in the partially saturated zone using a non-linear random walk in the space domain. The results of test simulations (cf.…”
Section: Transient Fluid Flow In the Partially Saturated Zonementioning
confidence: 99%
See 4 more Smart Citations
“…The LAST-Model (Sternagel et al, 2019) is based on the Lagrangian approach of Zehe and Jackisch (2016), which was introduced to simulate infiltration and soil water dynamics in the partially saturated zone using a non-linear random walk in the space domain. The results of test simulations (cf.…”
Section: Transient Fluid Flow In the Partially Saturated Zonementioning
confidence: 99%
“…2). A comparison of HYDRUS 1-D and the LAST-Model based on plot scale tracer experiments showed that both models perform similarly in case of matrix flow dominated tracer transport; however, under preferential flow conditions, LAST better matched observed tracer profiles indicating preferential flow (Sternagel et al, 2019). 40 https://doi.org /10.5194/hess-2020-527 Preprint.…”
Section: Introduction 25mentioning
confidence: 99%
See 3 more Smart Citations